0047 Poor health, lifestyle, work-related factors and premature loss of employment in older workers – results from the health and employment after fifty (heaf) study. (21st August 2017) - D'Angelo, Stefania; Syddall, Holly; Ntani, Georgia; Harris, E Clare; Linaker, Cathy; Stevens, Martin; Walker-Bone, Karen; Palmer, Keith T
Abstract : Background: Populations of Western countries are ageing; in response to this, governments encourage longer working lives. However, many workers leave paid employment prematurely. We have examined the combined importance of poor health, lifestyle and work-related characteristics as risk factors for health-related job loss among older workers. Methods: 8134 men and women aged 50–64 were recruited from 24 English general practices to the HEAF study. Participants provided information on their socio-demographic, lifestyle, health (self-rated health, depression, chronic disabling musculoskeletal pain, severe difficulties in daily activities), and employment characteristics. Those in paid employment at baseline were categorised at 1 year follow-up as: 'still in work and didn't change job on health grounds' (n=4, 232) versus 'not in work due to health reasons (n=101)'. The remaining participants were excluded from this analysis. Multivariate Poisson regression with robust standard errors was used to analyse the data. Results: All ill-health measures were strongly associated with health-related exit from the workplace (RR for poor self-rated health=4.5, (95%CI 3.1, 6.6)). Adjustment for smoking, leisure-time physical activity (LTPA) and job dissatisfaction attenuated these associations (RR for poor self-rated health=3.1, (95%CI 2.0, 4.8)). Smoking, lack of LTPA, and job dissatisfaction (RR=5.4; (95% CI 3.4, 8.5)) were associated with health-related job loss independently of health variables. Conclusions: Poor self-rated health, depression, chronic disabling musculoskeletal pain and severe problems with daily activities significantly increased the risk of leaving employment on health grounds. Tackling unhealthy behaviours and improving job satisfaction could reduce the risk of exiting the workforce for older workers with poor health.